Analysis of the socio-demographic state of rural areas in the system of their sustainable development: a case study of Ukraine - Dziamulych, Mykola; Petrukha, Serhii; Yakubiv, Valentyna; Zhuk, Oksana; Maiboroda, Oksana; Tesliuk, Sofiia; Kolosok, Andrii (University of Agronomic Sciences and Veterinary Medicine of Bucharest, 2021)
In the article we have substantiated and conducted statistically assess the impact of the final results of economic activity on the current socio-demographic situation of rural areas in Ukraine. Based on the results of determining the influence of conditioned factors on the level of labour migration of the rural population in Ukraine, we have developed a regression equation. Also, based on the results of the study, we built two cartograms, comparison of which provides an opportunity to assess the dynamics of the formation of the total fertility rate in rural areas (per 1 woman) for 2016 – 2020. We built a cartogram that visualizes the results of grouping regions of Ukraine by natural increase, decrease population in rural areas of Ukraine. The results of our study provide an opportunity to confirm that in the context of Ukraine’s official accession to the European Union and the serious challenges of today, the Ukrainian state should perform the functions of regulating the most important spheres of society in general and rural areas in particular. The task of increasing the employment of the rural population should be raised to the level of state priorities, which would provide an opportunity to create new jobs for the rural population in industries that can provide the maximum competitive effect.
Keywords: socio-demographic state; rural population; sustainable development; rural areas